(untitled) (REMUNOM, 2023)
It is known that some bacteria are directly related to important infectious conditions in the oral cavity and require greater attention from dental surgeons, such as Escherichia coli and Enterococcus faecalis, which may be related to cases of periodontitis, endodontic infections and even peri-implantitis. This highlights the need to apply effective alternative therapies against these pathogens, such as phytotherapy. The aim of this study was to evaluate the literature on the use of phytotherapy in the treatment of oral infections caused by bacterial strains of Escherichia coli and Enterococcus faecalis. Given the pre-existing literature, it is understood that the application of herbal medicine in dentistry has shown promising results and is an effective alternative for the treatment of bacterial oral infections caused by Escherichia coli and Enterococcus faecalis. In addition, the use of natural products, whether in the form of essential oils, extracts or other presentations, represents a coadjuvant tool in the fight against infections caused by multidrug-resistant microorganisms, and this is a low-cost, accessible practice that has fewer side effects compared to conventional pharmacological treatments. It is suggested that further review studies be carried out on this subject in order to identify and evaluate the effectiveness of the application of phytotherapy against other types of pathogens.